Implementation Of Criminal Law For Communities That Conduct Activities Outside The Home During The Covid-19 Pandemic In Indonesia - Firman Freaddy Busroh; Fatria Khairo (International Journal of Artificial Intelligence Research, 2022)
The Covid-19 pandemic has become a very dangerous infectious disease with so many deaths globally. Through the National Disaster Management Agency, the government then coordinates to suppress disasters resulting from the Covid-19 pandemic by implementing social distancing and physical distancing policies. But unfortunately, there are still many violations among the public in following this policy, such as going out of the house carelessly when there are restrictions. Therefore, it is necessary to have a policy from the government against violators of this regulation. This research will use a statute approach and a conceptual approach. The study results found that the Indonesian government had made various efforts to prevent the spread of Covid-19 and implemented different new laws to prevent the spread of Covid-19. Several government policies that support this effort are the implementation of work from home, social distancing, etc. Finally, there are also criminal sanctions given to people who are not in line with government policies through article 212, article 216, and article 218 of the Criminal Code.